2001
DOI: 10.1074/jbc.m104067200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Cysteine Residues of ThiI in the Generation of 4-Thiouridine in tRNA

Abstract: The enzyme ThiI is common to the biosynthetic pathways leading to both thiamin and 4-thiouridine in tRNA. We earlier noted the presence of a motif shared with sulfurtransferases, and we reported that the cysteine residue (Cys-456 of Escherichia coli ThiI) found in this motif is essential for activity (Palenchar, P. M., Buck, C. J., Cheng, H., Larson, T. J., and Mueller, E. G. (2000) J. Biol. Chem. 275, 8283-8286). In light of that finding and the report of the involvement of the protein IscS in the reaction (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
135
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(139 citation statements)
references
References 37 publications
4
135
0
Order By: Relevance
“…The first one regards the source of sulfur atoms. A well-established thiolation mechanism, occurring in the case of s 2 U34 (MnmA) and s 4 U8 (ThiI) formation in tRNAs, involves a persulfide carried by an active site cysteine as the sulfurating agent (8)(9)(10). The 3D structure of TtuA allows us to exclude such a mechanism, because no free cysteine, as a potential site for a catalytic persulfide, can be observed in the active site (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The first one regards the source of sulfur atoms. A well-established thiolation mechanism, occurring in the case of s 2 U34 (MnmA) and s 4 U8 (ThiI) formation in tRNAs, involves a persulfide carried by an active site cysteine as the sulfurating agent (8)(9)(10). The 3D structure of TtuA allows us to exclude such a mechanism, because no free cysteine, as a potential site for a catalytic persulfide, can be observed in the active site (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was removed and immediately frozen on dry ice and stored until assayed (Ͻ24 h). Dehydratase was assayed in two steps for the formation of pyruvate according to the procedure described by Gardner and Fridovich (44 (30).…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…2, s 4 U) involves the transfer of sulfane sulfur from Cys 328 of IscS to a cysteine of the ThiI protein (27)(28)(29). ThiI, in turn, binds tRNA, activates a specific uridine using Mg-ATP, and transfers the sulfur, during which it is oxidized to a disulfide (30). The synthesis of 2-thiouridine requires IscS in vitro (31) and in vivo (15,25,26) and may be similar to s 4 U synthesis with the MnmA protein as the recipient of the IscS persulfide (31).…”
mentioning
confidence: 99%
“…The mechanism involves mobilization of sulfur from cysteine by IscS in the form of an enzyme-bound persulfide (23,24), which is then transferred to a cysteine residue on ThiI before final insertion into U8 of tRNA (25)(26)(27). The nature of the final sulfur transfer step is unclear, but it has been recently shown that ThiI is oxidized to a disulfide under single turnover conditions (28). Thus, ThiI has the multiple roles of binding tRNA, activating O4 of uridine 8 using Mg-ATP while accepting a sulfur atom from IscS and transferring it to the 4-position to give the final product, s 4 U.…”
mentioning
confidence: 99%